Traditional Rainwater Management (Haveli cultivation) for Building System Level Resilience in a Fragile Ecosystem of Bundelkhand Region, Central India - Singh, Ramesh; Akuraju, Venkataradha; Anantha, K. H.; Garg, Kaushal K.; Barron, Jennie; Whitbread, Anthony M.; Dev, Inder; Dixit, Sreenath (Frontiers in Sustainable Food Systems, 2022)
This paper presents the evidence on how traditional rainwater management system (haveli system) has been contributed towards rehabilitating degraded landscapes into productive condition in Bundelkhand region of Central India. The haveli system was the lifeline of the region for water security since 300 years. Farmers (~ 1-5%) situated at the upstream of the landscape were harvesting surface runoff in their fields during monsoon by constructing earthen embankment along with provision to drain out water after receding of the monsoon. ICRISAT and consortium partners have introduced innovative approach of haveli rejuvenation by constructing masonry core wall along with outlet at suitable location. Total 40 haveli structures were constructed between 2010 and 2021 across seven districts of Bundelkhand region. One of the pilot sites (i.e., Parasai-Sindh) was intensively monitored to capture the landscape hydrology, change in land use, cropping intensity and crop productivity between 2011 and 2017. Out of 750 mm rainfall received during July and Sept, generated surface runoff is about 135 mm (19% of rainfall) on an average. However, rainfall below 450 mm (dry years) rarely generates surplus water as most of the rainfall received in such years are absorbed within the vadose zone. Whereas, wet years with over 900 mm rainfall, generates runoff about 250-300 mm (~ 30-35%). Rejuvenation of haveli system created opportunity to harvest surface runoff within farmers field which helped to improve groundwater levels in shallow dug wells (additional by 2-5 m hydraulic head) which was remain available during following years. This has enhanced cropping intensity by converting about 20% of permanent fallow lands into productive agriculture and ensured irrigation availability especially during critical crop growth stage. This enhanced land and water use efficiency of the system and increased household net income by two to three folds compared to baseline status. This paper further establishes the link between landscape rejuvenation through haveli system, groundwater resource availability, production system and household income in the fragile ecosystem of Central India. The results are helpful for various stakeholders to take informed decisions on sustainable natural resource management.